1998 Summer High School Transportation Institute. - North Carolina Agricultural and Technical State University. Transportation Institute (Greensboro, N.C. : North Carolina A&T State University, 1998)
Includes Appendix A : application and brochure -- Appendix B : 1998 schedule of activities -- Appendix C : student handbook.
"September 1998."
"... creates an awareness of the attractive career choices and opportunities existing within the transportation industry."
Final report.
Mode of access: Internet.
Keywords: Transportation -- Study and teaching -- North Carolina; Transportation -- Vocational guidance